THE MODULE DEVELOPMENT OF REALISTIC MATHEMATICS APPROACH TO IMPROVE NUMBER PROBLEM SOLVING ABILITY - Natalia Sipayung, Tetty; Anzelina, Dewi (Studies in Comparative Education, 2018)
This study was conducted to know; (1) the validity of module development in realistic mathematics approach to improve the ability of solving problem in numbers; (2) the learning effectiveness of using realistic mathematics approach module to improve solving problem ability in numbers. This study used Dick and Carry development model. The subject was VII-B grade students of Nusantara Lubuk Pakam 2018/2019, while the object was the realistic mathematic approach module. The module was based on four problems solving indicators, including: understanding problem, devising plan, carrying out the plan and checking back the obtained result. The result showed that realistic mathematic approach module was valid based on the media standard, including the graphic aspect with 3.87 average score and the language aspect with 3.76 average score. Further, based on the material standard reviews, content expediency rose with 3.71 of the average score, 3.97 for presentation aspect and 4 for contextual scoring aspect. In addition, using realistic mathematic approach module was effective in enhancing the problem solving ability. The learning effectiveness was analyzed based on the students’ activity and teachers’ ability in maintaining the learning process and the students’ problem solving ability. The average score for students’ activity was 3.8 and 4.27 for teachers’ ability in maintaining the learning process, categorized as good 7. Meanwhile, the result of students’ problem solving ability test using realistic mathematic approach module showed 75.49 score which was higher than learning without using module, 57.59 score.